Everyday religion observing modern religious lives - Ammerman, Nancy Tatom 1950- (Oxford University Press, 2007)
"Nancy T. Ammerman has assembled a diverse and interdisciplinary group of scholars to provide a critical observation of modern religion in action. This collection of previously unpublished essays approaches modern religion at its most fundamental levels and brings the reader into the presence of religious practice among the complexities of daily life. The authors take aim at the failure of secularization theories to explain why and how people continue to choose religion in the midst of modernity. Each essay combines portrait of religious activity in often unexpected places with an evaluation of currently dominant theories to offer a fresh alternative perspective. From media to politics to family and civic life, these scholars look for the ways religion crosses boundaries and compare its effects in different cultural and institutional situations."--Jacket.